Educating for science. Elements to define an education policy that supports the training of scientists. The case of Mexico. - Francisco Javier Segura Mojica; Hugo Alejandro Borjas García (Arizona State University, 2014)
This article analyzes the structure and recent changes in the Mexican educational system. It characterizes some of the variables that relate to education research, and concludes with a review of studies that have recently been developed to identify patterns in the research training process. This paper will, in general terms, outline strategies to improve the training of researchers in México.